Metabolic and endocrine changes induced by cinnamon in women with polycystic ovarian syndrome: A pilot study - Sepideh Peivandi; Sahar Heydari-latibari; Fatemeh Ghasemzadeh; Marzieh Zamaniyan; Adele Bahar; Hadi Majidi; Behnam Maleki (Mashhad University of Medical Sciences, 2024)
Objective: Most polycystic ovary syndrome (PCOS) patients have metabolic abnormalities in which insulin resistance (IR) plays a pivotal role. Cinnamon is a herbal medicine with insulinotropic properties. This pilot study aimed to evaluate the effects of cinnamon on ovarian volume, androgenic profile, and metabolic and anthropometric parameters in women with PCOS.Materials and Methods: A single-center, double-blind, randomized, placebo-controlled trial was carried out on 39 overweight / obese women with PCOS. For six months, subjects in the cinnamon (500 mg) (n=19) and placebo (n=20) groups were given three capsules daily. Before and after the intervention, the variables were assessed. The data was analyzed using the GraphPad Prism software.Results: After the intervention, the two intervention and control groups had significant differences in abdominal subcutaneous fat and ovarian volume, but they did not differ significantly in terms of body mass index (BMI). Also, after the intervention, no significant difference was observed between the two groups in terms of lipid profile and the concentration of androgenic biomarkers of insulin resistance.Conclusion: Cinnamon supplementation improves ovarian volume and subcutaneous abdominal fat but has no effect on anthropometric parameters, lipid profile, insulin resistance, or androgen hormones.